The meaning of the diakon word group in John 12:26 applied to the ministry in congregations - Breed, Gert (2014)
This article investigates the meaning of the diakon word group in the Bible with the focus on the use of this word group in the Gospel of John. John 12:26 is considered in depth. The results of this investigation reveal important differences from other recent research on this word group. The results of the research are then applied to the ministry in congregations.
Keywords: Diakoneo; Gospel of John; John 12:26; Congregation; Diakonia; Diakonos; follow; glorify; Honour; Love; Messenger; Ministry; Service